(untitled) (Journal of Mechanical Engineering, 2014)
In this experimental investigation cryogenically treated zinc coated diffused brass wire and cryogenically treated plain brass wire have been used as cutting tool. In this experimentation AISI D3 die steel has been taken work piece. The input process parameters considered are pulse width, time between two pulses, wire mechanical tension and wire feed rate. Taguchis L9 orthogonal array has been used for design of experiments. The process performance is measured in terms of optimization of material removal rate. After performing the experiment, results of both wires have been compared. It is found that the cryogenically treated zinc coated diffused brass wire gives good material removal rate as compare to cryogenically treated plain brass wire. DOI: http://dx.doi.org/10.3329/jme.v43i2.17827